Density functional theory calculations of the stress of oxidised (1 1 0) silicon surfaces. (4th November 2016) - Melis, C; Giordano, S; Colombo, L; Mana, G
Abstract: The measurement of the lattice-parameter of silicon by x-ray interferometry assumes the use of strain-free crystals. This might not be the case because surface relaxation, reconstruction, and oxidation cause strains without the application of any external force. In a previous work, this intrinsic strain was estimated by a finite element analysis, where the surface stress was modeled by an elastic membrane having a 1 N m −1 tensile strength. The present paper quantifies the surface stress by a density functional theory calculation. We found a value exceeding the nominal value used, which potentially affects the measurement accuracy.